Evaluation of yield and quality of virgin coconut oil produced using repeated batch fermentation with baker’s yeast - Jasman; Lawe, Erlin Anastasia; Sudirman (Agriculture and Natural Resources, 2021)
Virgin coconut oil (VCO) produced using a repeated batch fermentation technique with baker’s yeast was assessed for quantity and quality changes as a result of repetitive fermentation. The application of repeated batch fermentation was expected to reduce the operating costs of small industries. The batch fermentation was performed continuously six times and the yield and quality of the VCO were assessed for each batch based on one-way analysis of variance followed by the Tukey test. The results showed that the average VCO yield of the six batches was 25.71±2.09% and it was significantly reduced as repeated fermentation increased. The mean values of the moisture content and the acid and peroxide numbers were 0.01±0.007%, 0.1±0.03% and 0.1±0.05 meq/100g, respectively. The moisture and acid number were not significantly (p > 0.05) affected by repeated fermentation, whereas the peroxide number was significantly different. Although the peroxide number increased, it was still within the SNI 7381-2008 standards. Three cycles of repeated fermentation were recommended for the best yield of VCO.